Fax to speech optical character recognition and speech synthesis - Florendo, Carlo F.; Garces, Maricar C.; Kim, Ji Myung L.; Layug, Oliver Dwight A.; Villapando, Vanessa Marie D. (2000)
In this report, we present an optical character recognition (OCR) system that enables the computer to recognize text from a faxed document or a bitmapped image. This system is capable of reading (i.e. recognizing and speaking aloud) text from faxed and bitmapped images. It is also capable of extracting only the textual information from a graphic document if the document contains both text and images. Image preprocessing is done by deskewing the graphic document. The skew angle is detected by the Hough transform. Once the document is skew normalized, the characters are segmented. Our segmentation algorithm extracts only the textual information from the document. We used heuristics to determine whether an object in the document is an image, noise, or a character. The detected images and noise are isolated from the document, thus, making it ready to be OCRed. The system recognizes the characters using a 3 layer fully connected feed forward network. The neural network was trained using the backpropagation algorithm. The system assumes that not all characters in the document are of the same font size. Thus, the need for size normalization. Normalization is done through simple linear transformations. This makes the system capable of recognizing characters of different font sizes. After normalization, the vector representation of the characters are fed to the neural network. The recognized characters are then fed into a speech engine for speech synthesis.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Optical character recognition devices; Speech synthesis